2011
DOI: 10.1093/humrep/der113
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive status in adult male long-term survivors of childhood cancer

Abstract: One-third of young adult male survivors of childhood cancer has elevated FSH levels. FSH appears to be a very sensitive marker for the need of assisted reproductive techniques in male childhood cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…While childhood cancer had an almost sevenfold increased odds of developing hypogonadism in adulthood compared with controls (Romerius et al, 2009), chemotherapy agents used to treat cancer were not found to be associated with development of hypogonadism (Puhse et al, 2011;Tromp et al, 2011). Total body irradiation was significantly associated with lower mean T level compared with controls in one study assessing a series of different cancer treatment modalities (b = À3.53; p = 0.036; Tromp et al, 2011).…”
Section: Disease-specific Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…While childhood cancer had an almost sevenfold increased odds of developing hypogonadism in adulthood compared with controls (Romerius et al, 2009), chemotherapy agents used to treat cancer were not found to be associated with development of hypogonadism (Puhse et al, 2011;Tromp et al, 2011). Total body irradiation was significantly associated with lower mean T level compared with controls in one study assessing a series of different cancer treatment modalities (b = À3.53; p = 0.036; Tromp et al, 2011).…”
Section: Disease-specific Studiesmentioning
confidence: 98%
“…Total body irradiation was significantly associated with lower mean T level compared with controls in one study assessing a series of different cancer treatment modalities (b = À3.53; p = 0.036; Tromp et al, 2011).…”
Section: Disease-specific Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were performed in paediatric stem cell transplantation or are retrospective analyses with a small number of cases [1,2,3,4,5,6,7]. The complications mentioned were mostly urological infections and haematuria [8].…”
Section: Introductionmentioning
confidence: 99%